Death in a Budapest butterfly - Buckley, Julia, 1964- (Buckley, Julia, 1964- Hungarian tea house mystery., 2019)
Hana Keller and her family run Maggie's Tea House, an establishment heavily influenced by the family's Hungarian heritage and specializing in a European-style traditional tea service. But one of the shop's largest draws is Hana's eccentric grandmother, Juliana, renowned for her ability to read the future in the leaves at the bottom of customers' cups. Lately, however, her readings have become alarmingly ominous and seemingly related to old Hungarian legends... When a guest is poisoned at a tea event, Juliana<U+2019>s dire predictions appear to have come true. Things are brought to a boil when Hana<U+2019>s beloved Anna Weatherley butterfly teacup becomes the center of the murder investigation as it carried the poisoned tea. The cup is claimed as evidence by a handsome police detective, and the pretty Tea House is suddenly endangered. Hana and her family must catch the killer to save their business and bring the beautiful Budapest Butterfly back home where it belongs.